Aplikasi Media Interaktif Sebagai Edukasi ASI Ekslusif pada Ibu Hamil di Posyandu Ngentak Bantul - Mita Meilani; Alief Nur Insyiroh Abidah; Risky Puji Wulandari (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2026)
Failure to provide exclusive breastfeeding contributes significantly to growth and developmental delays and a decline in infant health. The success of the exclusive breastfeeding program for infants aged 0 to 6 months is determined by various determinants such as family support and access to information, as well as internal factors such as the mother’s health condition, knowledge, and attitude also play a crucial role. The purpose of this community service activity aims to increase the knowledge of pregnant women about exclusive breastfeeding. So it is hoped that it can optimize the media in providing health education. The method used in this community service activity is to provide education or Health Education at the Ngentak Integrated Health Post (Posyandu) for 20 pregnant women. This community service activity provides material using leaflets. The results show that this activity can increase the knowledge of pregnant women about exclusive breastfeeding with an average pre-test score of 62.25 and an average post-test score of 85.25. The use of interactive media with leaflets as an educational tool has proven effective in conveying information about the importance of exclusive breastfeeding.